Secondary lesions in rabbits experimentally infected with Treponema pallidum. - Strugnell, R A (1986)
Thirty rabbits infected with 10(3) of either Nichols or Melbourne 1 strains of Treponema pallidum were observed for the development of secondary lesions, which appeared outside areas inoculated with viable treponemes. More rabbits infected with Melbourne 1 strain (eight of 15 rabbits) than were infected with the Nichols reference strain (three of 15 rabbits) developed secondary lesions. The mean (SD) incubation periods of secondary lesions were 52 (8) days for rabbits infected with Melbourne 1 and 56 (4) days for rabbits infected with Nichols strain. These mean incubation periods did not correlate with appreciably increased concentrations of immune complexes or glycosaminoglycans in the serum of infected rabbits.